Importance of pre‐anthesis anther sink strength for maintenance of grain number during reproductive stage water stress in wheat - JI, XUEMEI; SHIRAN, BEHROUZ; WAN, JIANLIN; LEWIS, DAVID C.; JENKINS, COLIN L. D.; CONDON, ANTHONY G.; RICHARDS, RICHARD A.; DOLFERUS, RUDY (Plant, cell and environment, 2010)
ABSTRACT Reproductive stage water stress leads to spikelet sterility in wheat. Whereas drought stress at anthesis affects mainly grain size, stress at the young microspore stage of pollen development is characterized by abortion of pollen development and reduction in grain number. We identified genetic variability for drought tolerance at the reproductive stage. Drought‐tolerant wheat germplasm is able to maintain carbohydrate accumulation in the reproductive organs throughout the stress treatment. Starch depletion in the ovary of drought‐sensitive wheat is reversible upon re‐watering and cross‐pollination experiments indicate that the ovary is more resilient than the anther. The effect on anthers and pollen fertility is irreversible, suggesting that pollen sterility is the main cause of grain loss during drought conditions in wheat. The difference in storage carbohydrate accumulation in drought‐sensitive and drought‐tolerant wheat is correlated with differences in sugar profiles, cell wall invertase gene expression and expression of fructan biosynthesis genes in anther and ovary (sucrose : sucrose 1‐fructosyl‐transferase, 1‐SST; sucrose : fructan 6‐fructosyl‐transferase, 6‐SFT). Our results indicate that the ability to control and maintain sink strength and carbohydrate supply to anthers may be the key to maintaining pollen fertility and grain number in wheat and this mechanism may also provide protection against other abiotic stresses.